Aggregate Efficiency Dynamics in Lithuanian Dairy Farms - Tomas Balezentis; Giannis Karagiannis (German Journal of Agricultural Economics (GJAE), 2021)
In this paper, we attempt to identify the major groups of decision making units (dairy farms) contributing to the aggregate efficiency change. We also suggest identifying influential peers in order to gain more insights into possible development strategies within a sector. The empirical application focuses on specialist dairy farms in Lithuania. The farm-level data cover the period 2004-2016. The results indicate the presence of structural changes and resulting shifts in the aggregate efficiency. Based on the results of decomposition of the covariance term and identification of the influential peers, two models can be followed by Lithuanian dairy farms, namely "pure" family farms with lower operational scale and large farms involving hired labour.
Keywords: 330; data envelopment analysis; aggregate efficiency; dairy farm; Lithuania